PENGEMBANGAN BUKU AJAR FISIKA OPTIK BERBASIS SOFT-SKILLS - Setya Ferywidyastuti (Pendidikan Kimia Unimus, 2019)
The textbook based on Soft-skills are targeted to create student-centered learning so that they can encourage students to learn more actively in solving problems and finding more independent sources of learning and improving the quality of Soft-skills contained in the process of applying the textbook. This research was conducted in the 1st Semester of Academic Year 2018/2019 in the Study Program DIII Refraction Optician (RO) STIKES HAKLI Semarang with the number of participants of 50 students. The research development (R & D) in this study aims to produce Optical Physics textbooks using the Soft skills. The stages of this research include define, design, develop and disseminate. The research design used in the trial application of this textbook was a quasi-experimental design with the form of pretest-posttest control group-design. The results of the study show that the development of Optical Physics textbook based on Soft-skills has gone through a validation process and has been stated to fulfill the content validity set by the expert, so the developed textbook is declared valid. Increasing student activity with an average score of 3.4 shows very active criteria that have a positive effect on the value of student learning outcomes. The results of the analysis of students’ questionnaire sheets showed that the learning process was fun and easy to understand the material taught with data 87,3% of students were happy and stated practical. The application of textbooks based on Soft-skills can significantly improve student learning outcomes and their Soft-skills.